Humour, Wit, and Society in Laurence Sterne’s Tristram Shandy (“The Author’s Preface”) - Flavio Gregori (University of Bucharest Review. Literary and Cultural Studies Series, 2023)
The present essay provides an analysis of humour in Laurence Sterne’s Tristram Shandy, exploring its various forms, functions, and meanings. After introducing the idea of the lex inversa of humour, which can be observed in Sterne’s unconventional storytelling style, it analyses the “Author’s Preface” that appears at the end of the third volume of the book rather than at its beginning. The essay compares the satirical criticism of modern introductions found in Jonathan Swift’s A Tale of a Tub and the humorous but balanced mixture of wit and judgment in Tristram Shandy’s Preface. It examines the evolution of the concept of humour in the eighteenth century and traces its various meanings in Sterne’s book, from ancient bodily theories to psychological character construction. It argues that Sterne’s portrayal of odd humours aligns him with those who depicted England as a land of freedom, where humour played a crucial role in challenging wrong societal norms and liberating humanity from hypocrisy. This sympathetic form of comedy portrays human flaws for communal laughter, promoting harmony and balance. After addressing the ambiguity surrounding the actual subject of Sterne’s “learned” satire, the essay concludes by emphasising Sterne’s wit as a form of his humour, especially in the paradoxical defence of wit in the “Author’s Preface”, which he contrasts with the false severity of the “grave folks”. The essay argues that Sterne’s humorous strategy provides society with a moral foundation of humanity, sociability, and freedom.